Geopolitics, Public Communication and Social Cohesion Facing the Crisis of Democracy: Risks and Challenges - Pérez Curiel, Concha; Rivas-de-Roca, Rubén (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In times of rising polarization and disinformation at the global level, this reprint, "Geopolitics, Public Communication, and Social Cohesion Facing the Crisis of Democracy: Risks and Challenges", explores the communication of the main conflicts that put integrity and geopolitics at risk. Drawing upon different methods, the contributions offer insightful findings on the role of communication by public institutions in crisis management and the actions of journalists and citizens. Therefore, this reprint furthers our understanding of how to deal with problems such as audiences' distrust in politics, citizens' disaffection with the media, and institutions' loss of credibility.